Tata Negara Indonesia di Tengah Ancaman Populisme: Implikasi terhadap Demokrasi dan Konstitusi (International Forum of Researchers and Lecturers, 2025)
Populism, which often puts forward anti-ite rhetoric and claims as a representation of the people's voice, can have a significant impact on the state administration system. This article aims to understand the extent to which populism can change the structure of state administration and test the resilience of the Indonesian democratic system and constitution in facing the challenges of populism. The method used in the preparation of this article is qualitative methodology with a literature review approach from various academic sources such as books, journals, relevant scientific papers. The results of the study show that populism gives challenges and threats to the state system and has a negative impact on democracy and implications for the constitution. Populism is a challenge for the Indonesian constitutional democratic system by damaging the checks and balances mechanisms, politicizing the law and state institutions, and the risk of eroding the supremacy of the constitution.